Peran Kesadaran Merek, Citra Merek, dan Keaslian Merek Terhadap Keputusan Pembelian Produk Kosmetik Halal BB Cream pada Konsumen Wardah di Kota Semarang Berbasis Kuisioner Online - Adelia Nirmala Cahya; Amron Amron; Vincent Didiek Wiet Aryanto; Ariati Anomsari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This research evaluated the impact of brand awareness, image, and authenticity on Wardah BB Cream purchasing decisions among 150 consumers. Using a quantitative approach and PLS-SEM analysis, the study results showed that all three factors made a significant positive contribution. Among the three, brand authenticity was found to be the most dominant factor driving consumers to make a purchase. These findings indicate that strengthening authenticity values ​​and consistent brand image play a crucial role in driving purchasing decisions for halal cosmetic products.